Pedro and the shark - Manushkin, Fran; Lyon, Tammie (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2017)
Pedro is excited for his class's trip to the aquarium, but when he gets separated from the others near the shark tank, he gets frightened and starts running to and fro--until he takes a hint from the shark to stop going in circles.
Pedro's jokes inside.
RL: K-2.
IL: K-2.
Keywords: Hispanic American boys -- Juvenile fiction; Public aquariums -- Juvenile fiction; School field trips -- Juvenile fiction; Sharks -- Juvenile fiction; Hispanic Americans -- Fiction; Aquariums -- Fiction; School field trips -- Fiction; Sharks -- Fiction; Lost children -- Fiction